Understanding the profile of a Nyaope addict and its connotations for law enforcement agencies - Dintwe, S. I. (Acta criminologica, 2017)
Drug addiction is a worldwide problem. Amongst a plethora of problems, drug addiction and how it should be dealt with, remains a big challenge for law enforcement agencies in South Africa and elsewhere. This is the reason why the South African Police Service has tried over years to develop and implement an intervention strategy on drug dealing, usage and addiction. Drug addiction and its resulting consequences tend to influence the different approaches adopted by the police. However, the majority of interventions by the police, the public sector, the private sector and civil society have proved to be inadequate and less effective in many countries, including South Africa. This ineffectiveness can, in the case of South Africa, be attributed to the policing approaches followed, as well as the nature of the interventions aimed at curbing drug addiction, particularly with reference to the increases in the use of the so-called drug ‘nyaope’.1 The current South African statistics for nyaope addicts and its consistent increase, is but one piece of evidence that these interventions are inadequate and less effective. The research problem is, therefore, anchored on the perception that the police appear to continue to rely on old strategies, even though nyaope use has only become popular in more recent times and brings its own unique challenges in comparison to other drugs that have been used for a very long time. A qualitative analysis was, therefore, conducted in South Africa in order to formulate a profile of nyaope addicts. It is postulated, therefore, that there should be a direct link between a nyaope addict profile and the policing strategy to be used to combat the use of this drug. This article draws on data generated from interviews conducted with law enforcers and investigators, those who are involved in the fight against drug addiction, interviews with nyaope addicts (and their families), as well as from literature pertaining to drugs. This research concludes that there is a discord between dealing with this problem and the policing strategies to combat drug abuse currently being adopted. It further concludes that the implications for the police include a need for a multi-faceted, multi-disciplinary and multi-departmental approach to the problem of nyaope addicts. Although there are a myriad of strategies, policies, working committees and legislation aimed at dealing with the problem of drug addiction, there is still a lack of co-ordination of these efforts. These are complicated by a popular belief that the police should deal with this problem on their own. Salient issues such as the apportioning of blame to the police, the absence of a social development component and fragmented intervention continue to defeat the purpose on drug addiction efforts and their effectiveness in dealing with nyaope addiction.